Partial harmonization of corporate taxes in an asymmetric repeated game setting - Jun-ichi Itaya; Makoto Okamura; Chikara Yamaguchi (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper investigates the conditions under which partial harmonization for capital taxation is sustained in a repeated interactions model of tax competition when there are three heterogenous countries with respect to their capital endowments. We show that regardless of the structure of the coalition (i.e., any group of countries), whether partial tax harmonization is sustainable or not crucially depends on the capital endowment of the median country relative to those of the large and small countries. The most noteworthy finding is that the closer the capital endowment of the median country to the average capital endowment of the large and small countries, the less likely is the tax harmonization including the median country to prevail and the more likely is the partial tax harmonization excluding the median country to prevail.
Keywords: H73; F59; F21; 330; tax coordination; asymmetric countries; repeated game; tax competition; Kapitalertragsteuer; Unternehmensbesteuerung; Steuerharmonisierung; Steuerwettbewerb; Wiederholte Spiele; Faktorproportionentheorem; Kapital; Theorie